2010
DOI: 10.1007/s11414-010-9224-9
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Substance Abuse Treatment Seeking Following Cocaine-Related Emergency Department Visits

Abstract: Chest pain is the most common medical complaint among cocaine-using emergency department (ED) patients. Correlates of substance abuse treatment seeking were examined using 3-month post-discharge surveys from 170 ED patients admitted with cocaine-related chest pain. Four treatment categories were specified as the dependent variable in an ordered logistic regression: no treatment (74.7%), informal treatment only (7.1%) formal treatment only (5.9%) both formal an informal treatment (12.4%). The following variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 40 publications
0
10
1
Order By: Relevance
“…Twelve studies that did not ask participants to rate directly the influence of stigma on their treatment-seeking decisions did use statistical methods to determine whether or not stigma predicted treatment motivation and/or utilization. 13 , 15 , 42 , 54 , 59 66 Of these, five found stigma to be a positive predictor or copredictor, 54 , 60 , 63 65 three found it to be a negative predictor or copredictor, 15 , 61 , 62 and three found it not to be a predictor at all. 13 , 42 , 59 …”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Twelve studies that did not ask participants to rate directly the influence of stigma on their treatment-seeking decisions did use statistical methods to determine whether or not stigma predicted treatment motivation and/or utilization. 13 , 15 , 42 , 54 , 59 66 Of these, five found stigma to be a positive predictor or copredictor, 54 , 60 , 63 65 three found it to be a negative predictor or copredictor, 15 , 61 , 62 and three found it not to be a predictor at all. 13 , 42 , 59 …”
Section: Resultsmentioning
confidence: 97%
“…The first study that found stigma to be a positive predictor found that stigma barriers significantly predicted treatment utilization at 3-month follow-up for cocaine users seen in the emergency room, while other types of treatment barriers did not. 60 The second study found that pregnant women in a detoxification program who reported an acceptability barrier (a category that included stigma) had increased treatment-motivation scores, while gestational age of the fetus was a negative predictor. 54 The third and fourth studies were different analyses of the same data.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These individuals frequent the emergency room due to chest pain, drug-induced psychosis, depression, overdose, vehicle accidents, or drug-seeking behavior [7,8]. ER users are more socioeconomically disadvantaged and use drugs more often than non-ER users [9].…”
Section: Introductionmentioning
confidence: 99%